Application of the Principle of Good Faith as an Effort to Protect the Law Against Borrowers in Online Lending Practices - Hanafie, Nurharsya Khaer; Firmansyah, Firmansyah (Universitas Islam Negeri Alauddin Makassar, 2025)
This study aims to examine the application of the principle of good faith in contractual agreements and to analyze the legal protection afforded to borrowers in online loan transactions under this principle. The core issue addressed is how the principle of good faith is operationalized in digital loan agreements and its implications for borrower protection. Employing a qualitative approach with a descriptive-analytical method, the research investigates legal instruments and practices governing online lending platforms in Indonesia. The findings reveal that the principle of good faith plays a pivotal role in ensuring fairness, transparency, and accountability in online credit transactions. This principle serves as a normative foundation for safeguarding borrowers’ rights, particularly within the framework of the Indonesian Civil Code, Law No. 11/2008 on Electronic Information and Transactions, and Financial Services Authority Regulation No. 6/POJK.07/2022. The study highlights the necessity of reinforcing good faith as a legal instrument to mitigate asymmetrical power relations and promote legal certainty in digital financial services. These findings imply the need for stronger regulatory enforcement and borrower education to foster equitable financial inclusion in the digital era.